Substrate-integrated waveguide cross-coupled filters with mixed electric and magnetic coupling structure. Issue 8 (8th June 2018) - Azad, Amit Ranjan; Jhariya, Dharmendra Kumar; Mohan, Akhilesh
Abstract: This paper presents a substrate-integrated waveguide (SIW) mixed electric and magnetic coupling structure implemented on a single-layer substrate to create finite transmission zeros (TZs), which can be used to design microwave filters with higher frequency selectivity. Mixed coupling is realized by three slot-lines on the top metal plane combined with an iris-window between two adjacent SIW cavities. The electric and magnetic coupling can be separately controlled by adjusting the dimensions of the slot-lines and the width of the iris-window, and a controllable TZ below or above the passband can be produced. Furthermore, a detailed analysis of the mixed coupling structure is presented. To demonstrate the validity of the proposed structure, third- and fourth-order cross-coupled generalized Chebyshev bandpass filters are designed and fabricated using the standard printed circuit board process. The experimental results are in good agreement with the simulation results. The filters exhibit simple structure and good frequency selectivity.